COMPARATIVE ANALYSIS OF PROBLEM STRUCTURE IN 6TH GRADE MATHEMATICS TEXTBOOKS IN TURKEY AND İRAN - FEIZIPOUR , Nesa; TAPAN BROUTIN , Menekşe Seden; ÖZDEMİR, M. Emin (SSD Journal, 2023)
In this study, the relationship between real life and the problems in 6th-grade mathematics textbooks in Turkey and Iran has been examined comparatively. The research analyzed the problems in the textbooks according to the PISA context category. In this study, which was determined as document analysis, one of the qualitative research approaches, the collected data were analyzed by content analysis. As a result of the findings, it was determined that the questions related to daily life in the 6 th-grade mathematics textbooks represented in both countries were quantitatively less than the total number of questions. According to the PISA context category of the problems in the Turkish and Iran textbooks, it is seen that the most personal problem and the least scientific and professional problem types are included. It is thought that the problems in the textbooks should be higher to embody mathematics, to enable students to better interpret where and how they should use mathematics in real life and be more successful in international exams. It is suggested that the problems in the textbooks should be associated with real-life situations and more space should be given to scientific and professional categories.